The effects of methamphetamine self-administration on behavioural sensitization in the olfactory bulbectomy rat model of depression - Kucerova, Jana; Pistovcakova, Jana; Vrskova, Dagmar; Dusek, Ladislav; Sulcova, Alexandra (The international journal of neuropsychopharmacology, 2012)
Depression is frequently comorbid with a drug addiction and may seriously complicate its treatment. Currently, there is no routinely used animal model to investigate this comorbidity. In this study the effect of repeated administration of methamphetamine on i.v. drug self-administration in an olfactory bulbectomy model of depression in rats was investigated in order to propose and validate a rat model of comorbid depression and addiction. Male Wistar rats were either olfactory-bulbectomized (OBX) or sham-operated. They subsequently underwent a methamphetamine sensitization regime, which consisted of daily i.p. injections of methamphetamine for a 14-d period; controls received Sal injections at the same frequency. The i.v. self-administration of methamphetamine (0.08 mg/kg in one infusion) paradigm on a fixed ratio schedule of reinforcement was performed using operant chambers. A significant decrease of the drug intake was recorded in sham-operated animals pretreated with methamphetamine when compared to the unpretreated group. This was not apparent in the OBX groups. Both groups of OBX animals exhibited a higher intake of methamphetamine compared to the corresponding sham-operated groups, thus confirming the hypothesis of higher drug intake in depressive conditions in this rodent model. The procedure of behavioural sensitization to methamphetamine decreased the number of self-administered drug doses per session in the sham-operated rats. It is hypothesized that this phenomenon resulted from increasing efficacy of the drug after behavioural sensitization caused by repeated methamphetamine intermittent administration.
Keywords: Disease Models, Animal; deprese; modely nemocí na zvířatech; Depression; Male; Rats; návykové chování; Treatment Outcome; potkani Wistar; autoaplikace; Animals; Self Administration; zvířata; mužské pohlaví; výsledek terapie; krysa rodu Rattus; Rats, Wistar; methamfetamin; Behavior, Addictive; Olfactory Bulb; Methamphetamine; bulbus olfactorius